PERANCANGAN MESIN AMPLAS DUDUKAN BELT DENGAN MENGGUNAKAN MOTOR PENGGERAK LISTRIK 125 WATT - Rahmat Adisucipto Mamuka; Zuldesmi Zuldesmi; Denny D. Maukar (Pendidikan Teknik Mesin, 2022)
ABSTRACT It is well known that the grinding result with a grinding machine is more efficient because it speeds up the processing time of the workpiece. Overall, it can be said that the results of the grinding test using a grinding machine are more effective and efficient, because in addition to the relatively faster duration of work, the grinding results obtained on the workpiece are smoother and more evenly distributed throughout. It is known that the results of manual tests are quite time-consuming, this can be seen from the results obtained. And the results of the first experiment of manual grinding with a duration of 60 seconds, the average speed generated is 109.76 m/s longer compared to a grinding machine with 100.50 m/s. With a duration of 120 seconds the average speed is 100.53 m/s and with the grinding machine 99.00 m/s and finally with a duration of 180 seconds the average speed with manual grinding is 100.15 m/s and with the grinding process with a 97.00 m/s, so the media or workpiece looks rougher and the overall surface is uneven. Keywords: 125 Watt Electric Motor, Manual Sanding